2015
DOI: 10.1103/physrevb.91.235416
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal plasma spectrum of graphene interacting with a thick conductor

Abstract: Self-consistent field theory is used to obtain the non-local plasmon dispersion relation of monolayer graphene which is Coulomb-coupled to a thick conductor. We calculate numerically the undamped plasmon excitation spectrum for arbitrary wave number. For gapped graphene, both the lowfrequency (acoustic) and high frequency (surface) plasmons may lie within an undamped opening in the particle-hole region. Furthermore, we obtain plasmon excitations in a region of frequency-wave vector space which do not exist for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 58 publications
8
32
0
Order By: Relevance
“…The proper mathematical formalism to include the surface plasmon interacting with a 2D layer was first presented by Horing et al 20 Detailed numerical investigation of the plasmon excitation for such systems demonstrated the extended regions of undamped plasmons. 50 In addition, the work reported by Mikhailov 29 on voltage-tunable THz emitter relies on a structure to perform a periodic spatial modulation to the velocity of an incident electron beam. This modulation can be realized by introducing a biased metallic grating adjacent to the electron beam.…”
Section: Discussionmentioning
confidence: 99%
“…The proper mathematical formalism to include the surface plasmon interacting with a 2D layer was first presented by Horing et al 20 Detailed numerical investigation of the plasmon excitation for such systems demonstrated the extended regions of undamped plasmons. 50 In addition, the work reported by Mikhailov 29 on voltage-tunable THz emitter relies on a structure to perform a periodic spatial modulation to the velocity of an incident electron beam. This modulation can be realized by introducing a biased metallic grating adjacent to the electron beam.…”
Section: Discussionmentioning
confidence: 99%
“…(17), the linear dispersions and their prefactor scalings are the same as those for graphene. 68 However, the two independent bandgaps, ∆ SO and ∆ z , play unique roles in shaping the hybrid-plasmon branches when the damping from different PHMs is considered. It is found that the outer PHM's boundaries are only determined by ∆ < and the two hybrid-plasmon group velocities (slopes) are proportional to G and √ G. These two group velocities drop to zero as ∆ SO and ∆ z increase since G 4 √ 2αv…”
Section: A Approximate Analytical Resultsmentioning
confidence: 99%
“…68,[73][74][75][76] Furthermore, our previous work studied the plasmon instability in the graphene double-layer system, predicting an instability-based terahertz emission, 77 and nonlocal plasmons in a metal-graphene-metal encapsulated structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Creating pristine graphene in commercial quantities with a specific band gap is a major challenge in its use for nanoelectronic devices. Some of the intriguing properties which have received a great deal of attention include the doping and temperature dependence of plasmon excitations and their energy dispersion dependence on the direction of the wave vector in the Brillouin zone for graphene [10][11][12][13][14][15], the Klein paradox [16][17][18][19], the Veselago lens [19][20][21], screened impurity potential [22,23], effect of magnetic field [22] to name just a few.…”
Section: Introductionmentioning
confidence: 99%